Broadening Financial Indicators in the Special Data Dissemination Standard. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
In December 2008, the IMF Executive Board discussed the Seventh Review of Data Standards Initiatives, and Directors requested staff to return to the Board within about a year with a proposal for the inclusion of selected financial indicators in the Special Data Dissemination Standard (SDDS). This paper responds to the 2008 request taking into account recent developments. The recent financial crisis has heightened the need for policymakers, financial regulators and capital market participants to put in place conditions that would help prevent the occurrence of similar crises in the future. One of the areas identified by the international community as key in crises prevention is the availability of timely and more detailed financial data that could provide early warning signals of impending risks and vulnerabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet